IDENTIFICATION OF AGARWOOD SAPWOOD CHEMICAL COMPONENTS FROM FUNGAL INOCULATION RESULTS ON Gyrinops versteegii (Gilg.) DOMKE PLANTS - Mega, I Made; Kartini, Ni Luh (International Journal of Biosciences and Biotechnology; Vol 8 No 1 (2020): Vol. 8 No. 1, September 2020DO - 10.24843/IJBB.2020.v08.i01.p05)
Agarwood is one of non-timber forest product comodites (NTFPs) which has high economic value and as an export commodity. Agarwood produce an aromatic resin substance in the form of lumps that located between the wood cells in various shapes and colors. According to Indonesian National Standards, the category of agarwood is classified into several levels such as agarwood sapwood, kemedangan, and agarwood powder. The classification system is based on color, weight, and aroma. This classification method shows that the current quality of agarwood welding systems is still subjective. Therefore, more objective welding system is needed which is related to the chemical composition and resin content. This study objective is to identify the chemical components of agarwood sapwood from the results of fungal inoculation in agarwood-producing plants of gyrinops versteegii. The research conducted by extracting agarwood sapwood sample using acetone. This agarwood sapwood sample collected from the result of Fusarium, Rhizopus and Trichoderma fungi inoculation for 1 year. Furthermore, the agarwood acetone extract fractionated with a gradient column chromatography with hexane-ethyl acetate eluent. The method to identify the compounds/component is using chromatography gas-spectro-photometer mass (GC-MS). The results showed that the chemical components contained in agarwood from fungal inoculation were mostly in the form of ester compounds. The highest types compounds and the highest density compound were found in agarwood produced by Trichoderma fungi inoculant, namely Hexanedioic acid, dioctyl ester; 11-octadecanoic acid, methyl ester; Cyclopropanedodecanoic acid, 2-octyl-, methyl ester; 9-octadecanoic acid, methyl ester; Octadecanoic acid, 9.10- dihydroxy-, methyl ester; Cyclopropanepentanoic acid, 2-undecyl-, methyl ester; Pentadecanoic acid, 14-methyl-, methyl ester; and non-ester compounds, namely: 2-tridecenI-ol; 2- (2 ’, 4’, 4 ’, 6’, 6 ’, 8’, 8’Heptamethyltetrasiloxan -2 ’; 3-Hydroxybutanamide. 8- methoxy-2- (2.